The effect of authentic leadership on organizational communication: the mediating role of psychological well-being - Naiboğlu, Gülsu; Bilgivar, Orkun Osman; Bilgivar, Orkun Osman (Sakarya Üniversitesi, 2022)
The purpose of this research is to determine the mediating role of psychological well-being in the effect of authentic leadership on organizational communication. For this purpose, the opinions of 439 teachers working in Istanbul in the 2020-2021 academic year were consulted. Hypotheses related to the model, which was created based on the theoretical framework, were tested by establishing the research. In the research, "correlation design," one of the quantitative research designs, was used, and Baron and Kenny's four-stage model was used to create and test the model. "Authentic Leadership Scale," "Communication Competence Scale," and "Psychological Well-Being Scale" were applied to the participants in the study. As a result of the research, it was found that authentic leadership highly affects organizational communication; It has been determined that psychological well-being has a partial mediating role in the significant positive effect of authentic leadership on organizational communication. In the research, according to the gender of the teachers, in the opinions of school administrators on communication competencies; shows that male teachers are higher than female teachers. In the research, according to the educational status of the teachers, the psychological well-being of undergraduate teachers was lower than that of graduate teachers. The most striking finding of the study is that authentic leadership highly affects organizational communication.
Keywords: Authentic leadership; Organizational communication; Psychological well-being; Educational organizations